(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: The effects of exercise on plasma lactic acid level and body temperature following a standardized meal were carried out on 20 healthy young individuals (aged between 18 and 29 yrs.), consisting of 10 males and 10 females. The physical fitness of the subjects was determined measuring their blood pressure, pulse rate and other physical examinations. Methodology: Each subject was made to ride the bicycle ergometer for 6mins, at a rhythmic cadence of 50revolution/ min via 100beats metronome counts. Blood samples were collected before and after the exercise to analyze for the pre and post exercise plasma lactate levels. Pre and post-exercise values for body temperature were also measured. Statistical tests were carried out at 95% CI (P=0.05). Result: The result obtained showed that exercise causes a statistically significant increase (p< 0.05) in both plasma lactate concentration (from a pre-exercise mean value of 0.98 ±0.07mmol/L to post- exercise mean value of 2.84 ±0.21mmol/L) and body temperature (from a mean value of 36.45 ±0.130C before exercise to a mean value of 36.91 ±0.190C after exercise). Conclusion: There was a statistically significant increase in plasma lactateand body temperature because of exposure to exercise which is in line with findings from most previous studies. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.270-274